Nursing guidelines for patients after kidney transplantation: Integrative review - Leandro, Camila Trindade; Saito, Katya Araújo Machado; Furlan, Maryana da Silva; Aquino, Vera L cia Andrade de (Brazilian Journal of Transplantation, 2019)
Introduction: In recent years, chronic kidney disease (CKD) has been substantially increasing. With it, the number of patients on the waiting list for a transplant has increased. Thus, it is necessary that nurses are trained to provide assistance to patients from the pre-transplant phase through hospital discharge and outpatient follow-up. Purpose: To assess evidence available in the literature on nursing guidelines for kidney transplant patients. Methods: This is an integrative literature review carried out from March to October 2019. Search and collection of data was performed by online access to the CAPES and VHL Portal using descriptors in Health Science (Decs): Kidney transplantation, standards, nursing. Inclusion criteria used were: articles in full, in Portuguese, English and Spanish, published from 2014 to 2018. Results: Among 344 articles selected, 331 were eliminated for not following the purpose and inclusion criteria, and 13 articles were analyzed. Conclusion: The study showed the importance in the direct care of nurses in assisting kidney transplant patients, guiding them as to the importance of immunosuppressive treatment, food care, healthy lifestyle habits in order to provide a better quality of life and avoiding graft loss and even the death of patients.